A siker reménye és a kudarc okai : Egyetemalapítások a középkori Magyarországon - Font, Márta (Per Aspera ad Astra, 2017)
The study focuses on the circumstances of establishing of medieval Hungarian universities and analyses the problems of their short period of activity. The author applied many different points of view for the comparing first Hungarian university with the contemporary foundations in the neighbour countries. The author followed the comparative method also in the case of later founded Hungarian universities and made own conclusions. The latest research results on the field of history of universities were also used in the study.